2009
DOI: 10.1002/pd.2236
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the duration of pregnancy termination with vaginal misoprostol for fetal abnormality

Abstract: Three factors: nulliparity, younger maternal age and increasing gestation, were associated with abortion prolongation. Apart from musculoskeletal abnormalities, the fetal anomaly had no impact on abortion duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
14
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 14 publications
7
14
1
1
Order By: Relevance
“…A longer time interval in women with a previous caesarean section in the study of Wagner could be due to the absence of a previous spontaneous delivery [9]. In the study by Dickinson, higher maternal age was associated with an increased requirement for surgical intervention, which is consistent with the reports of Ashok et al [28]. Sak et al, studied the factors influencing the duration of misoprostol-induced abortion in the second trimester and found the induction-to-abortion interval to be longer in patients with hyperglycemia and advanced gestational age [30].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A longer time interval in women with a previous caesarean section in the study of Wagner could be due to the absence of a previous spontaneous delivery [9]. In the study by Dickinson, higher maternal age was associated with an increased requirement for surgical intervention, which is consistent with the reports of Ashok et al [28]. Sak et al, studied the factors influencing the duration of misoprostol-induced abortion in the second trimester and found the induction-to-abortion interval to be longer in patients with hyperglycemia and advanced gestational age [30].…”
Section: Discussionsupporting
confidence: 83%
“…For example, there were three main factors which influenced the duration of the abortion in a study by Dickinson and Doherty. Increasing gestational age, nulliparity, and advanced maternal age were associated with prolongation of the abortion [28]. In the study by Wagner, the parameters with significant influence were gestational age at the time of induction, obstetric history, and nulliparity.…”
Section: Discussionmentioning
confidence: 99%
“…GA affects the entire abortion process, including the I-to-A interval and completion of abortion. While pregnancy termination before 17 weeks of gestation was associated with higher chances of incomplete abortion [24], the mean I-to-A interval increases by 4 h after 20 weeks' gestation [7]. Supporting previous data [7], our results indicated that TOP after 24 weeks was associated with an increased risk of prolonged I-to-A interval.…”
Section: Discussionsupporting
confidence: 81%
“…As mifepristone is not available in Turkey, misoprostol is the first-line abortifacient in most settings. Misoprostol, a prostaglandin E1 analogue, has been used for induction of abortion at second and third trimesters since 1997 [7]. Misoprostol has many advantages including stability at room temperature, ease of administration, different administration routes, and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge about the abortion interval (AI) and associated influencing factors is important for counseling women who need termination of a second trimester pregnancy; however, few studies mention such findings [4,5], and the inclusion criteria in these studies merely includes cases with fetal anomalies or selected medical indications. Thus, the aim of this retrospective study was to estimate the AI in all enrolled women who needed medical termination by a combination of vaginal and oral misoprostol and to identify the factors that affect the AI.…”
Section: Introductionmentioning
confidence: 99%